2015
DOI: 10.5505/tjtes.2015.64494
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of morphine–midazolam versus morphine injection for pain relief in patients with limb fractures - a clinical trial

Abstract: BACKGROUND: Pain relief, using opiates as a primary choice, is an important part of treating limb fractures. Yet, in order to reduce opiate consumption, other combinations have been introduced. This study aimed to compare pain reduction by a combination of morphine-midazolam with morphine injection in patients with limb fractures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 29 publications
0
1
0
Order By: Relevance
“…The results of this assessment showed that there is no significant difference between the two groups. So findings of that research show that morphine does not change the pain relief effect of morphine in combination with midazolam (26). Additionally, the experimental studies reveal conflict data about the combinative effect of midazolam and opioid (27)(28)(29).…”
Section: Discussionmentioning
confidence: 88%
“…The results of this assessment showed that there is no significant difference between the two groups. So findings of that research show that morphine does not change the pain relief effect of morphine in combination with midazolam (26). Additionally, the experimental studies reveal conflict data about the combinative effect of midazolam and opioid (27)(28)(29).…”
Section: Discussionmentioning
confidence: 88%